Sintesis Membran Silika Untuk Pengolahan Limbah Rhodamin B Variasi Komposisi Poly Etyhlen Glycol (PEG) - Mutia Yuli Rahmawati; Jhon Armedi Pinem; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Membrane is a selective and semipermeable layer that lies between two phases, namely feed phase and permeate phase. Membrane synthesis usingsilica with phase inversion method. The purpose of this research were to make membranes of silica for waste Rhodamin Bwith 0; 0,15; 0,30; dan 0,45 gram by weight PEG and operating pressure of 1, 3, and 5 bars. This research produced porous membrane. The characterization membranes analysis were SEM analysis, flux and rejection. Based on Flux and rejection results showed that membrane with 0,30 gram composition of PEGwith of porous is 0,056 μmwas the most effective performance with the flux operating pressure 1, 3, and 5 bar was 18,13 L/m2.h, 31,20 L/m2.h, 41,36 L/m2.h and rejection elimination of Rhodamin B was 81,15%, 59,62% and34,08%. Based on characterization of membrane permeability, selectivity, and porous statistic showed that membrane silica were proven as membrane ultrafiltration. With a range of flux of 10-50 L/m2.h and a range of porous of 0,001-0,1 μm.Keywords: phase inversion, membrane, waste Rhodamin B, ultrafiltration